Principal Strategies in Realized Hygienic Toilet Standardization in Elementary Schools - Nurfauziah, Astri; Yunus, Dede; Sutanto, Tono; Istiqomah, Yunita Yasmin; Iskandar, Sofyan (Papanda Publisher, 2025)
Clean and proper toilets are an important indicator in creating a healthy school environment and supporting the teaching and learning process. However, many elementary schools in Indonesia still do not meet hygienic toilet standards. This article aims to examine the role of principals' strategies in realizing hygienic toilet standards in elementary schools through a literature review. Using a literature review approach from various journals, policy reports, and educational documents, this article outlines six main strategies: planning and budgeting, facility standardization , maintenance systems, hygiene education, school committee involvement, and partnerships with external parties. It was found that participatory , visionary, and collaborative principal leadership is crucial to the success of the hygienic toilet program. This study contributes to the development of sustainable healthy school policies and enriches the literature on school-based management, particularly in the context of sanitation facility management as part of the principal's leadership responsibilities at the elementary level.